2014
DOI: 10.1021/jp504001u
|View full text |Cite
|
Sign up to set email alerts
|

Classical Density Functional Study on Interfacial Structure and Differential Capacitance of Ionic Liquids near Charged Surfaces

Abstract: We designed a coarse-grained model for aromatic ionic liquids [CnM IM + [T f2N − ] with cations containing different alkyl groups. Within the framework of correlation-corrected density functional theory, the interfacial structure of studied ionic liquids are compared over a range of surface charge densities, alkyl chain lengths and surface geometries. The nonpolar hydrocarbon chains on cation tend to stretch out on the neutral surface. Differential capacitance of electric double layer formed by ionic liquids i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
(128 reference statements)
1
19
0
Order By: Relevance
“…Across all degrees of ion pairing, the DC tends to be higher at a positive electrode potential compared to a negative one. The larger DC at the positive electrode is generally attributed to the greater ability of the smaller anion to screen surface charges [38]. However, a monotonic decrease is observed for the DC in general, across a wide potential range, with increasing amounts of ion pairing (Fig.11).…”
Section: Forces Between Charged Surfacesmentioning
confidence: 92%
See 1 more Smart Citation
“…Across all degrees of ion pairing, the DC tends to be higher at a positive electrode potential compared to a negative one. The larger DC at the positive electrode is generally attributed to the greater ability of the smaller anion to screen surface charges [38]. However, a monotonic decrease is observed for the DC in general, across a wide potential range, with increasing amounts of ion pairing (Fig.11).…”
Section: Forces Between Charged Surfacesmentioning
confidence: 92%
“…The parameter λ is determined by electroneutrality in the bulk (as the correlation hole represents the removal of the self contribution from the background) [30,38]. Unlike ion correlations are approximated with the functional,…”
Section: Electrostatic Correlationsmentioning
confidence: 99%
“…Differential capacitance is directly related to the capacity of EDLCs. A simulation of the electrode | IL interface was done to correlate the change of differential capacitance with surface potential (Vatamanu et al, 2010; Ma et al, 2014). It was also found that small ions, like Li + , in an IL solution will change the original ionic composition of the IL and construct different electrode | IL interfaces leading to a smaller differential capacitance compared with the one of the neat IL (Zhao et al, 2010).…”
Section: Supercapacitorsmentioning
confidence: 99%
“…Despite a large amount of theoretical and simulation work on the capacitance of RTILs in porous electrodes, , little is known about how the properties of EDLCs containing RTIL mixtures would be affected by the electrolyte composition. Toward the rational design of the electrolytes and electrode materials, it would be desirable to understand the following: How would the EDL structure and capacitance change with the composition of RTIL mixtures? What is the microscopic mechanism underlying the capacitance change?…”
mentioning
confidence: 99%